Red Hat Certified System Administrator (RHCSA) exam prep video workshop - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Pearson IT Certification, 2016)
"Red Hat Certified System Administrator (RHCSA) Exam Prep Workshop contains hours of deep-dive training on common RHCSA exam traps, pitfalls, and difficulties. Sander van Vugt, an experienced Red Hat instructor, trainer, and author will detail the most common mistakes people make when taking the exam, so you can avoid them in the testing facility. You will then walk through a live practice exam with the author in real time, so you can experience first-hand what it's like to take the test. The videos consist of live trainer discussions, CLI presentations and demos, and a real-time practice exam walk-through. You will also learn about the structure of the exam, what to do when you're stuck, how to approach questions and track time, and more. You can find comprehensive coverage of the RHCSA exam in the Red Hat Certified System Administrator (RHCSA) Complete Video Course and the Red Hat RHCSA/RHCE 7 Cert Guide, both available for Pearson IT Certification."--Resource description page.
Title from title screen (viewed October 26, 2015).
Presenter, Sander van Vugt.
Keywords: Linux -- Examinations; Electronic data processing personnel -- Certification; Red Hat, Inc; Electronic books